KESABARAN CINTA UMMU HABIBAH BERBUAH SURGA - Hadidjah, St. (Pusat Studi Gender dan Anak, IAIN Palu, 2017)
Umm Habibah bint Abu sufyan was Ramlah, her heart has been guided by divine guidance, then she abandoned the religion of her father ( abu sufyan) and she married to a man who does not bow to an idol for sure impending Rasullulah.When the pagan quraysh increased violence to the follower of the prophet, the muslim migrated to habasyah. In the group there ramlah bint abu sufyan along with her husband ubaidillah bin Jaksi al asadi, but unfurnately in a move ubaidillah bin Jaksi Al Asadi apostate he embraced chirtianity. There apostasy husband, umm habibah faced three options, namely,first go back to widowed at migrated place.For the sake of belief whice has been embedded in her heart, umm habibah choose widowed abasyah. Patience in the widowed and Far away from relitives, recorded with Allah Al Migthy. Umm habibah dreamed of being a mother of the faithful, and the dream turned into reality, she actually spoken by the prophed and became one of the mother of the faithful.